Factors Towards Entrepreneurial Orientation Among UTHM Students - ching, chao quan; Atan @ Yaakub, Siti Anisah (Research in Management of Technology and Business, 2024)
Entrepreneur is commonly seen as an innovator, a source of new ideas, goods services, and business/or procedures. Universities now play a larger role in encouraging entrepreneurship among students, which has resulted in the creation of fresh approaches, unique cultures, and structures. The limited number of resources and support networks available to UTHM students is difficult in encouraging an entrepreneurial orientation. Besides, lack of consideration dedicated to ethnic and social factors presents another difficulty in analysing the relationship between factors and entrepreneurial orientation among UTHM students. The main objective of this study is to identify the factors towards entrepreneurial orientation among UTHM students and to determine the relationship between factors and entrepreneurial orientation among UTHM students. The scope of this study is FPTP students who currently studying in UTHM. Quantitative method was used to gather data from the targeted respondents. The online survey form was distributed to 320 respondents to obtain data on factors toward entrepreneurial orientation. The SPSS statistical software was used in analysing data gathered. The factors towards entrepreneurial orientation among university students are autonomy, innovativeness, proactiveness and risk-taking. The level of autonomy, innovativeness, proactiveness and risk-taking was moderate. The findings show the autonomy, innovativeness, proactiveness and risk-taking have relationship with the entrepreneurial orientation. The outcome of this study can be used as input to FPTP UTHM in designing entrepreneurship programs.